2022
DOI: 10.1021/acs.jafc.2c02850
|View full text |Cite
|
Sign up to set email alerts
|

Krill Oil Turns Off TGF-β1 Profibrotic Signaling in the Prevention of Diabetic Nephropathy

Abstract: Diabetic nephropathy (DN), a severe microvascular complication of diabetes mellitus (DM), results in high mortality due to the lack of effective interventions. The current study investigated the preventive effect of krill oil (KO) on DN using a type 2 DM mouse model induced by streptozotocin and high-fat diet for 24 weeks. The diabetic mice developed albuminuria, mesangial matrix accumulation, glomerular hypertrophy, and fibrosis formation, with an increase in renal proinflammatory, oxidative and profibrotic g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…KO has been reported to have anti-inflammatory, anti-oxidative, and anti-fibrotic activities in mouse models of diabetic complications [ 11 , 12 , 27 ]. We previously found that KO could inhibit DM-induced cardiac and renal inflammation and fibrosis, preventing diabetic cardiomyopathy and nephropathy in a mouse model of T2DM [ 11 , 12 ]. In line with these findings, in the present study, KO was found to attenuate cutaneous inflammation in the diabetic wounds ( Figure 3 ).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…KO has been reported to have anti-inflammatory, anti-oxidative, and anti-fibrotic activities in mouse models of diabetic complications [ 11 , 12 , 27 ]. We previously found that KO could inhibit DM-induced cardiac and renal inflammation and fibrosis, preventing diabetic cardiomyopathy and nephropathy in a mouse model of T2DM [ 11 , 12 ]. In line with these findings, in the present study, KO was found to attenuate cutaneous inflammation in the diabetic wounds ( Figure 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, different from the anti-fibrotic effect of KO on the diabetic hearts and kidneys, KO generated cutaneous fibrosis in the diabetic mice ( Figure 5 ). In particular, KO activated the cutaneous expression of TGF-β1, α-SMA, and collagen as the initiator, intermediate product, and end product of fibrosis ( Figure 5 ), respectively, whereas TGF-β1 signaling and the expression of α-SMA and collagen were significantly inhibited by KO in the diabetic hearts and kidneys [ 11 , 12 ]. The discrepancy between the effects of KO on fibrosis in different tissues might be attributed to the different cell identities during the pathogenesis of diabetic complications.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations